IKAN AIR TAWAR ENDEMIK SUMATRA YANG TERANCAM PUNAH (The freshwater fishes of endemic of Sumatra that threatened species) - Sunarya Wargasasmita (Jurnal Iktiologi Indonesia, 2002)
From 589 species freshwater fishes recorded as inhabitant of freshwater ecosystem in Sumatra, 58 species (9.8%) belong to endemic species for Sumatra. The highest endemicity by family is Belontiidae (42.3%). Based on list of aquatic biota species represented in ’’The 2000 IUCN Redlist of Threatened Species” (IUCN 2001), can be identified 14 species of freshwater fishes of Sumatra that belong to threatened species. Of these, 7 species (50%) are endemic to Sumatra i.e. Betta burdigala, B. chloropharynx (found only in Bangka Island), B. miniopinna dan B. spilotogena (found only in Bintan Island), Neolissochilus thienemanni (found only in Lake of Toba), Poropuntius tawarensis and Rasbora tawarensis (found only Lake of Laut Tawar). Geographic distribution of those endemic species were analysed by province as unit analysis. The high endemicity by province are West Sumatra (24.1 %), Jambi (20.7 %), Riau Islands (17.3 %), Nanggro Aceh Darussalam (17.3 %), and Riau (15.5%). However, nowadays those high endemicity threatened by various development activities. Factors that threaten the existence of those species were identified. AbstrakDari 589 jenis ikan air tawar yang tercatat sebagai penghuni ekosistem perairan tawar Sumatra, 58 jenis diantaranya (9,8%) termasuk kelompok ikan endemik Sumatra. Suku yang mempunyai endemisitas tertinggi adalah Belontiidae (42,3%). Berdasarkan daftar jenis biota air yang tercantum dalam “The 2000 IUCN Redlist of Threatened Species (IUCN 2001), dapat diidentifikasi 14 jenis ikan air tawar Sumatra yang terancam punah (threatened species) dan 7 jenis diantaranya (50%) adalah jenis-jenis ikan endemik Sumatra yaitu Betta burdigala, B. chloropharynx (hanya terdapat di P. Bangka), B. miniopinna dan B. spilotogena (hanya terdapat di P. Bintan), Neolissochilus thienemanni (hanya terdapat di D. Toba), Poropuntius tawarensis dan Rasbora tawarensis (hanya terdapat di D. Laut Tawar). Distribusi geografis ikan endemik Sumatra dianalisis dengan provinsi sebagai unit analisis. Provinsi yang memiliki endemitas tinggi adalah Sumatra Barat (24,1 %), Jambi (20,7 %), Kepulauan Riau (17.3 %), Nanggro Aceh Darussalam (17.3 %), dan Riau (15,5%). Endemisitas yang tinggi tersebut sekarang terancam oleh berbagai aktifitas pembangunan. Diidentifikasi pula faktor-faktor yang mengancam kelangsungan hidup ikan-ikan tersebut.